Measurement-based care implementation by K-12 public school clinicians: A mixed-methods proof of concept study - Elizabeth H. Connors; Sophia Selino; Daniel Almirall; Nicolina Fusco; Jacob K. Tebes (Implementation Research and Practice)
Background This study assessed the feasibility and acceptability of a multilevel, multi-component implementation strategy for measurement-based care (MBC) called Feedback and Outcomes for Clinically Useful Student Services (FOCUSS). FOCUSS includes six components selected in our prior work with a national sample of school mental health stakeholders. This is among the first demonstrations of MBC with school-employed clinicians. We explored proof of concept by observing MBC adoption rates achieved by the end of the school year and other related implementation outcome data. Method A mixed-method, single-arm pilot study was conducted during one academic year with 10 school-employed mental health clinicians in two K-12 public school districts in Connecticut. Clinician adoption was assessed by monthly fidelity monitoring of measures clinicians entered in the feedback system. Clinician self-reported practices, attitudes, feasibility, acceptability, and appropriateness of using MBC with K-12 students was assessed by pre-training, 3-, 6-, and 9-month surveys. School year-end qualitative interviews explored clinician implementation experiences using MBC and FOCUSS implementation supports to inform future changes to FOCUSS in a district-wide trial. Results Clinicians were asked to implement MBC with five students; 60% of the clinicians achieved or exceeded this target, and MBC was adopted with 65 students. Other implementation outcomes were comparable to related studies. Qualitative feedback indicated that MBC is clinically valuable in schools by providing consistency and structure to sessions, is compatible with school mental health, and well regarded by students and parents. FOCUSS implementation supports were regarded as helpful, and individual performance feedback emails appeared to be a necessary component of FOCUSS to boost post-training implementation. Conclusion This is among the first studies of MBC implementation with school-employed mental health professionals in the United States. Results demonstrate proof of concept for MBC implementation with school social workers, psychologists and counselors and support subsequent district-wide use of FOCUSS to install MBC in schools.